Vasopressin but Not Oxytocin Responds to Birth Stress in Infants - Fill Malfertheiner, Sara; Bataiosu-Zimmer, Evelyn; Michel, Holger; Fouzas, Sotirios; Bernasconi, Luca; Bührer, Christoph; Wellmann, Sven (Frontiers in Neuroscience, 2021)
Context Birth triggers a large fetal neuroendocrine response, which is more pronounced in infants born vaginally than in those born by elective cesarean section (ECS). The two related peptides arginine vasopressin (AVP) and oxytocin (OT) play an essential role in peripheral and central stress adaptation and have a shared receptor mediating their function. Elevated cord blood levels of AVP and its surrogate marker copeptin, the C-terminal part of AVP prohormone, have been found after vaginal delivery (VD) as compared to ECS, while release of OT in response to birth is controversial. Moreover, AVP, copeptin and OT have not yet been measured simultaneously at birth. Objective To test the hypothesis that AVP but not OT levels are increased in infants arterial umbilical cord blood in response to birth stress and to characterize AVP secretion in direct comparison with plasma copeptin. Methods In a prospective single-center cross-sectional study, we recruited healthy women with a singleton pregnancy and more than 36 completed weeks of gestation delivering via VD or ECS (cesarean without prior uterine contractions or rupture of membranes). Arterial umbilical cord blood samples were collected directly after birth, centrifuged immediately and plasma samples were frozen. Concentrations of AVP and OT were determined by radioimmunoassay and that of copeptin by ultrasensitive immunofluorescence assay. Results A total of 53 arterial umbilical cord blood samples were collected, n = 29 from VD and n = 24 from ECS. Ten venous blood samples from pregnant women without stress were collected as controls. AVP and copeptin concentrations were significantly higher in the VD group than in the ECS group (both p < 0.001), median (range) AVP 4.78 (2.38–8.66) vs. 2.38 (1.79–3.88) (pmol/L), copeptin 1692 (72.1–4094) vs. 5.78 (3.14–17.97), respectively, (pmol/L). In contrast, there was no difference in OT concentrations (pmol/L) between VD and ECS, 6.00 (2.71–7.69) vs. 6.14 (4.26–9.93), respectively. AVP and copeptin concentrations were closely related (Rs = 0.700, p < 0.001) while OT did not show any correlation to either AVP or copeptin. In linear regression models, vaginal delivery and biochemical stress indicators, base deficit and pH, were independent predictors for both AVP and copeptin. OT was not linked to base deficit or pH. Conclusion Vaginal birth causes a profound secretion of AVP and copeptin in infants. Whereas AVP indicates acute stress events, copeptin provides information on cumulative stress events over a longer period. In contrast, fetal OT is unaffected by birth stress. Thus, AVP signaling but not OT mediates birth stress response in infants. This unique hormonal activation in early life may impact neurobehavioral development in whole life.